Prevalence and pattern of echocardiographic abnormalities among patients on haemodialysis at an urban hospital in Central Uganda - Kansiime, Grace; Kalyesubula, Robert; Okello, Emmy; Ocama, Ponsiano (African Journal of Nephrology, 2020)
Background: Cardiovascular disease is the most common cause of morbidity and premature mortality in patients on chronic haemodialysis. There are limited data on cardiac abnormalities among these patients in sub-Saharan Africa, including Uganda. We determined the prevalence and patterns of echocardiographic (echo) abnormalities among patients with end-stage renal disease (ESRD) on haemodialysis at Mulago National Referral Hospital, Kampala, Uganda. Methods: Eighty patients with ESRD on chronic haemodialysis were enrolled in the study over a period of five months from November 2017 to March 2018. Wecollected data on demographic and baseline clinical characteristics by reviewing charts and conducting patient interviews. Participants had blood pressure measurements performed and blood samples taken for laboratory investigations. We then conducted a cardiac evaluation using standard transthoracic echo protocols. Bivariable and multivariable analysis was performed to study associations with left ventricular hypertrophy and diastolic dysfunction. Results: Fifty-three of the 80 patients (66%) were male, mean age was 49 ± 16 years and the median duration on dialysis was 9.5 months (interquartile range 4–24 months). Twenty-eight (35%) had to travel >50 km to access dialysis. Seventy-four patients (93%) had at least one cardiac echo abnormality and 30% had at least three abnormalities. Left ventricular hypertrophy (68%) and diastolic dysfunction (64%) were the most common abnormalities. There was a high prevalence of factors that have previously been associated with left ventricular hypertrophy and diastolic dysfunction including anaemia (79%), poorly controlled hypertension (79%) and dyslipidaemia (56%) but none of these was statistically significantly associated in this study. Conclusions: Our study confirmed a high prevalence of cardiac abnormalities among a young population of African patients with ESRD on chronic dialysis. We recommend that echocardiography be part of the routine care to help plan early intervention for those at high risk of cardiovascular events.